Presence of a Vanadium Nitrogenase in Azotobacter paspali - Fallik, Elazar (1993)
There have been no previous studies on the genetics of Azotobacter paspali, an aerobic bacterium which forms a highly specific diazotrophic association with Bahia grass (Paspalum notatum). We constructed A. paspali strains defective in the molybdenum nitrogenase so that alternative N(2)ases could be studied. The cosmid vector pTBE and genomic DNA fragments (∼50 kb) of A. paspali ATCC 23367 were used to construct a gene library in Escherichia coli. Recombinant cosmids containing sequences homologous to molybdenum nitrogenase nifDK structural genes were identified by hybridization. A 2.9-kb fragment bearing the putative nifDK genes of A. paspali was subcloned and mutagenized in vitro by the insertion of a kanamycin resistance gene cassette. The mutation was recombined into the chromosome of A. paspali with the suicide vector pCU101. One resultant mutant strain, AP2, was incapable of diazotrophic growth in a molybdenum-containing medium (Nif(-)) without vanadium but grew well in a molybdenum-deficient medium with vanadium. The nitrogenase system in AP2 reduced acetylene to ethylene and produced ethane as 2.4% of the total products. Molybdenum levels as low as 10 nM prevented the diazotrophic growth of AP2, even in the presence of vanadium at levels up to 10 μM. These results are consistent with the existence of a vanadium nitrogenase system in A. paspali.